MULTIFACTORIAL ANALYSIS OF NEUROLOGICAL DETERIORATION IN CHILDREN WITH SPINAL TRAUMA AFTER SURGICAL TREATMENT - Batpenov N.D.; Baindurashvili A.G.; Vissarionov S.V.; Abdaliyev S.S. (Scientific Journal of Pedagogy and Economics, 2020)
The article presents a multifactorial analysis of assessing the dynamics of neurological deficit in pediatric patients with unstable complicated thoracic and thoracolumbar spine fractures. The effect of the terms of surgery that has passed from the moment of injury, as well as the severity of the damage to the spinal cord and its elements, has been studied in details. Magerl spinal fractures classification was implemented to evaluate the type of spine fracture, neurological deterioration were evaluated according to the international ASIA scale. Longest result follow-up period was 5 years after surgery. Surgical treatment of 36 patients at the age of 3 years to 17 years with unstable thoracic and thoracolumbar spine fractures complicated by neurologic deficit were performed. Longest result was monitored for up to 5 years in all patients. It was in studies revealing that a full recovery of neurological functions in children with complicated spinal fractures is noted during surgical treatment in the first 6-12 hours from the time of trauma, with the main cause of neurological deficit associated with compression of the spinal cord.